Weightlifting coaches' and athletes' understanding of injury prevention programs: a case study of Lumajang and Malang - Atmagara, Muhammad Izzan; Hanief, Yulingga Nanda (CV Rezki Media, 2025)
Background: Weightlifting is a high-intensity sport with a high risk of injuries due to improper technique, insufficient warm-up, and excessive training loads. Objectives: This study explores the understanding, strategies, and barriers of weightlifting coaches and athletes in Lumajang District and Malang City related to implementing injury prevention programs in performance sports. Methods: This study used a qualitative case study approach. Participants were selected using purposive sampling, consisting of weightlifting coaches with at least one year of experience and athletes who had trained and competed at the regional level. Data were collected through interviews, observations, and document analysis, while data were analyzed using the Miles and Huberman model, including reduction, presentation, and conclusion. Results: The results showed that coaches and athletes emphasized dynamic warm-ups, core and back strengthening exercises, and correct lifting techniques as the main strategies to prevent injuries. However, limitations in facilities, literature access, and training variety were identified as barriers to implementing optimal injury prevention programs. Conclusions: This study concludes that effective injury prevention in weightlifting requires structured warm-up routines, individualized training programs, and adequate supporting equipment. Strengthening coaches’ knowledge and providing better facilities are crucial to minimize injuries and enhance athlete performance.